2016
DOI: 10.3857/roj.2016.01669
|View full text |Cite
|
Sign up to set email alerts
|

The response of thrombosis in the portal vein or hepatic vein in hepatocellular carcinoma to radiation therapy

Abstract: PurposeThe purpose of current study is to evaluate the response of the patients with portal vein thrombosis (PVT) or hepatic vein thrombosis (HVT) in hepatocellular carcinoma (HCC) treated with three-dimensional conformal radiation therapy (3D-CRT). In addition, survival of patients and potential prognostic factors of the survival was evaluated.Materials and MethodsForty-seven patients with PVT or HVT in HCC, referred to our department for radiotherapy, were retrospectively reviewed. For 3D-CRT plans, a gross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Initial concerns about radiation-induced liver disease (RILD) limited enthusiasm for RT in this patient population; however, as more data regarding dose-volume risk parameters become available [8] , [9] , [10] , there has been increasing interest in the use of RT for patients with locally advanced or otherwise unresectable HCC, including those with PVTT [6] , [7] , [11] . Older studies suggested a potential, though modest, survival benefit with RT for these patients [12] , [13] , [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Initial concerns about radiation-induced liver disease (RILD) limited enthusiasm for RT in this patient population; however, as more data regarding dose-volume risk parameters become available [8] , [9] , [10] , there has been increasing interest in the use of RT for patients with locally advanced or otherwise unresectable HCC, including those with PVTT [6] , [7] , [11] . Older studies suggested a potential, though modest, survival benefit with RT for these patients [12] , [13] , [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Other radiotherapy methods include proton beam therapy, intensity-modulated radiotherapy, and stereotactic radiotherapy. Using 3D-CRT to treat 47 patients with HCC and PVTT, Bae and coworkers [ 77 ] obtained a response rate of 40%, median survival time of 8 months, and 1-year survival rate of 15%. Also using 3D-CRT, Rim and coworkers [ 78 ] reported a partial response rate of 55.6%, stable disease rate of 31%, progressive disease rate of 6.7%, and complete remission rate of 6.7%.…”
Section: Monotherapies and Associated Prognosismentioning
confidence: 99%
“…Until now, we cannot determine whether the gastroduodenal toxicities developed as a consequence of RT or occurred spontaneously due to cirrhosis and PHG. Severe hematemesis by aggravation of pre-existing PHG was reported in HCC patients receiving 3DCRT regardless of radiation dose [ 48 ]. Considering that V25 or V35 of gastroduodenum were significant dosimetric parameters affecting severe gastroduodenal toxicity in two studies, the application of IMRT would reduce gastroduodenal toxicity in HCC patients by sparing the high dose regions of the gastroduodenum as mentioned above [ 45 , 47 ].…”
Section: Dosimetric Studiesmentioning
confidence: 99%